2021
DOI: 10.1002/ijop.12806
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a mother during the COVID‐19 national lockdown in Italy: Issues linked to the wellbeing of pregnant women

Abstract: The COVID‐19 pandemic and consequent lockdown represent risk factors for the mental health of pregnant women. We explored the impact of COVID‐19 restriction policies on psychological health, analysing the predictive role of social support on maternal wellbeing. A total of 212 pregnant women recruited from two public hospitals in Italy were divided into two groups: (a) a pre‐COVID‐19 group composed of 141 expectant women (mean age = 34.6; SD = 4.3) at their third trimester before the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
5
8
0
Order By: Relevance
“…While, in the few studies conducted to assess the Italian prevalence of perinatal depression, a highly variable prevalence was observed ranging from 1.6 to 26.6%, even though all of these studies were carried out before the COVID-19 pandemic indeed ( 42 , 56 58 , 64 ). Our findings are in line with previous published (both international and Italian) studies carried out during the COVID-19 pandemic which reported significantly higher depression rates in pregnant women than studies conducted before the pandemic, with a prevalence ranging from 30 to 43% ( 16 , 18 , 29 , 31 , 53 , 65 71 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While, in the few studies conducted to assess the Italian prevalence of perinatal depression, a highly variable prevalence was observed ranging from 1.6 to 26.6%, even though all of these studies were carried out before the COVID-19 pandemic indeed ( 42 , 56 58 , 64 ). Our findings are in line with previous published (both international and Italian) studies carried out during the COVID-19 pandemic which reported significantly higher depression rates in pregnant women than studies conducted before the pandemic, with a prevalence ranging from 30 to 43% ( 16 , 18 , 29 , 31 , 53 , 65 71 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, within this framework, experiencing stressful and subjectively perceived traumatic events, during the perinatal period, may predispose women to the onset of de novo psychopathological manifestations, also in not predisposed pregnant and puerperal women ( 26 ). Therefore, one could argue that the COVID-19 pandemic and related restrictive measurements may have more likely represented a stressful and cumulative traumatic variable which might have modified the psychopathological trajectory in pregnancy and postpartum period, as already reported in the general population ( 27 , 28 ) and in samples constituted by pregnant and postpartum women ( 18 , 29 31 ). In fact, the gradual shaping in health care access and services due to the lockdown and restrictive regulations imposed by governments, including limitations in the access to gynecological, obstetrician and perinatal care and the restricted (or interrupted) possibility for partner and/or family member(s) of pregnant and puerperal women to assist them during pregnancy follow-ups, the delivery and postpartum period, significantly determined a psychological distress, an increased uncertainty and indeed fueled feelings of fears, anxiety and worries among pregnant and postpartum women ( 32 34 ).…”
Section: Introductionmentioning
confidence: 88%
“…Negative affect included: anxiety, worry, insomnia, fear, lack of energy and depression. This experience was also consistent with results from similar recent studies conducted in different countries (Kornilaki, 2021; Smorti et al, 2021). Death of close relatives included any mention of death of grandparents, relatives or friends' relatives.…”
Section: Resultssupporting
confidence: 93%
“…Without a doubt, we are experiencing an extremely difficult public health challenge due to COVID‐19 (Panchal et al, 2021). The prolonged lockdowns are causing a wide variety of mental health issues, such as anxiety (Kornilaki, 2021; Smorti et al, 2021), stress, insomnia and feelings of social isolation (Landmann & Rohmann, 2021), which are detrimental to individuals' well‐being (Beckes & Sbarra, 2022). In addition, prolonged lockdowns and social distancing guidelines have disrupted the dynamics of families and couples (Feeney & Fitzgerald, 2022).…”
Section: Autobiographical Memory and Gratitudementioning
confidence: 99%
“…Therefore, our ndings suggest that increased levels of perinatal depression may be experienced during the COVID-19 pandemic, more likely due to isolation and quarantine experience, also by pregnant and puerperal women, independently by pre-existing psychiatric disorders. Moreover, our sample is more representative of perinatal period comprising the third trimester of pregnancy and the rst postpartum trimester, hence, one could argue that our ndings might potentially re ect the effect of the COVID-19 pandemic during this period and that higher levels of perinatal depression observed in our sample might be due an effect dependent on the perinatal stage, as already documented in previous studies (Schwartz and Graham, 2020;Smorti et al 2021). In fact, according to these studies, the risk of negative psychological consequences during the COVID-19 pandemic may be increased especially in pregnant women in their third trimester who foresee delivery during the pandemic, as they may experience elevated stress and anxiety due to the potential adverse outcomes on the foetus and the infant (Rashidi Fakari and Simbar, 2020; Schwartz and Graham, 2020; Smorti et al 2021).…”
Section: Discussionsupporting
confidence: 55%